Thermal performance of wood wool cement panels as building envelope in hot- humid tropics - Loo, Ar Kok Hoo (2017)
Environmental problems are gaining momentum by the days. Construction industry consumes 10% of all our energy usage, building and their production contribute over 50% of CO2 emission in the production of cement, bricks and steel. These materials are used as building envelopes, which is the single largest architectural element in all buildings. Therefore, it is timely for the industry to source for suitable and sustainable alternatives. The Thesis had identified Wood Wool Cement Panels (WWCP) having such potential as alternative material. The objectives of the thesis are threefold, i.e. to investigate 1. Thermal performance of WWCP as external envelopes and compare it with conventional brick and plaster wall as building envelopes. 2. Validation of a suitable simulation software for performance comparison. 3. Comparing performance of WWCP versus conventional houses. WWCP has been used as one of the building materials in temperate countries but not common in Malaysia. The methodology involved test cells field measurements and computer simulations. Two Test Cells were constructed in Universiti Putra Malaysia (UPM), one with WWCP envelope and the other with conventional brick and plaster. Field measurements over four months to monitor air temperatures, relative humidity, air properties and solar gains, followed by validation of IES<VE> software. Thereafter IES was utilized to further assess the performance of WWCP in the context of passive Terrace and Semi-Detached Houses, which are common housing prototypes in Malaysia. The results were tabulated, analysed and discussed. The key findings on air temperature, mean radiant temperature, relative humidity, heat transfer and conduction gains had established WWCP comparable to, and in certain areas, performed better than conventional brickwall in thermal performance as evidenced in Test Cells, Terrace and Semi-Detached Houses results. Since there are few known researches on WWCP, the Thesis contributes significantly to provide valuable information for local building industry, policy makers, authority, and researchers on WWCP as an alternative building material suitable for the Tropics.